Decolonizing Cultural Heritage Theory: A Critical Reframing from the Palestinian Context - Ziad M. Shehada; Mohammed H Alaqad (WISE Pendidikan Indonesia, 2026)
This study examines how heritage conservation theories remain grounded in Eurocentric frameworks shaped by colonial and post-war Europe, including the Venice Charter, the Nara Document on Authenticity, and UNESCO conventions. While these agreements advanced global heritage discourse, they continue to marginalize indigenous, Islamic, and non-Western perspectives, particularly those impacted by conflict. Applying decolonial theory, the research reframes heritage paradigms by proposing a Palestinian philosophy rooted in local knowledge, community memory, and resistance practices. Central to this approach is the concept of “Liberation Heritage,” an anti-colonial model of cultural survival developed through literature, judicial texts, religious traditions such as Waqf, and heritage storytelling. This framework challenges Western notions of authenticity by emphasizing contextual values like living traditions, symbolic continuity, and cultural stewardship under occupation. Gaza, with its rich history and resilience amid suffering, serves as a primary case study for articulating this theory. Drawing on postcolonial thought, critical heritage studies, and Islamic architectural principles, the paper offers a constructive alternative for colonized or conflict-affected communities reclaiming cultural narratives. The findings contribute to broadening heritage theory, diversifying conservation practices, and empowering communities to assert their cultural sovereignty.